Sensitivity analysis of severe accident calculations for the estimation of CANDU-specific OILs. (March 2023) - Morreale, Andrew C.; Shah, Manit D.; Lebel, Luke S.; Brown, Morgan J.
Highlights: Sensitivity analysis of CANDU-specific operational intervention levels. Impact of MAAP-CANDU source term sensitivities on OILs. Sensitivities from MAAP-CANDU analysis assumptions and timing of releases can affect release mix and OIL (t, mix) curves. Despite variation, chosen OILs are still bounding and ensure reasonable response to accident conditions while maintaining public safety. Shortcomings for OIL7 addressed by including 89 Sr as extra marker radionuclide. Abstract: CANDU-specific operational intervention levels (OILs), were determined through extensive severe accident calculations with MAAP-CANDU, assessing a variety of postulated scenarios in single and multi-unit CANDU stations. OILs are simple, field-measurement criteria indicating the need for protective response actions (e.g., evacuation, relocation, food restrictions), and are derived from estimated radionuclide releases for various accident scenarios. Detailed OIL(t, mix) functions relate field measurements to generic dose limits, and are affected by the radionuclide release mix. Sensitivities to parameters in the severe accident calculations can affect radionuclide release mixtures, which may alter the OIL(t, mix) functions and could require adjustment of the OILs. The two categories of source term sensitivities are i) MAAP-CANDU analysis assumptions, and timing of releases (i.e. evolution of radionuclide releases over the accident). Despite some variation in the OIL(t, mix) curves from the sensitivities, the chosen OILs are still bounding and ensure reasonable response to accident conditions while maintaining public safety.